2015
DOI: 10.1038/srep17624
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides (OCPs) in wetland soils under different land uses along a 100-year chronosequence of reclamation in a Chinese estuary

Abstract: Soil profiles were collected at a depth of 30 cm in ditch wetlands (DWs), riverine wetlands (RiWs) and reclaimed wetlands (ReWs) along a 100-year chronosequence of reclamation in the Pearl River Delta. In total, 16 OCPs were measured to investigate the effects of wetland reclamation and reclamation history on OCP levels. Our results showed that average ∑DDTs, HCB, MXC, and ∑OCPs were higher in surface soils of DWs compared to RiWs and ReWs. Both D30 and D20 soils contained the highest ∑OCP levels, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 51 publications
1
19
1
1
Order By: Relevance
“…The levels of ∑OCPs (sum of the HCHs and DDTs) in the subsurface soils ranged 0.01–100.45 ng g −1 and were higher than the ND–32.7 ng g −1 in the surface soils (Table 1). Similarly, a slightly lower concentration of OCPs in the surface layer than the subsurface was reported from ditch wetlands of Chinese estuaries [6]. The ∑OCPs in this study were relatively lower than those of reported from soils of North Pacific Ocean (5.14–676 ng g −1 ) [21] and sediments of Weihe River, China (291.16 ng g −1 ) [14].…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…The levels of ∑OCPs (sum of the HCHs and DDTs) in the subsurface soils ranged 0.01–100.45 ng g −1 and were higher than the ND–32.7 ng g −1 in the surface soils (Table 1). Similarly, a slightly lower concentration of OCPs in the surface layer than the subsurface was reported from ditch wetlands of Chinese estuaries [6]. The ∑OCPs in this study were relatively lower than those of reported from soils of North Pacific Ocean (5.14–676 ng g −1 ) [21] and sediments of Weihe River, China (291.16 ng g −1 ) [14].…”
Section: Resultscontrasting
confidence: 41%
“…Dichlorodiphenyltrichloroethane (DDTs) and hexachlorocyclohexanes (HCHs) are among the extensively used OCPs in agriculture, public health, in controlling termite, tsetse fly and malaria causing mosquitoes [2,3,4,5]. Organochlorine pesticides are known for their ecological toxicity, high persistence and strong affinity to bioaccumulation [6,7]. Due to the high level of environmental toxicity and health impacts, the large-scale production and use of OCPs (HCHs and DDTs) is currently prohibited.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were manufactured and used for different purposes (e.g. as pesticides, flame retardant additives, transformer dielectric fluids) before they were legally banned [ 3 , 4 ]. Even though these products were produced for specific uses, they were also known for their adverse effects on the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the eco-exergy index was less sensitive to the sediment environment, and it displayed more integrity and generality than did the abundance index. Moreover, CCA showed that the OM was strongly correlated with the heavy metal contents in this study, except for those of Pb and Hg ( Figure 8 c), potentially because of the complex sources of OM and heavy metals in different regions [ 72 , 74 ].…”
Section: Discussionmentioning
confidence: 89%